Policy-Induced Migration in Canada: An Empirical Study - Day, Kathleen M.; Winer, S. (Stanley L.) (2001)
We investigate the influence of public policy on interregional migration in Canada using new interprovincial migration data constructed from personal income tax files for the years 1974 to 1996. We consider the consequences for gross and net migration flows of regional variation in employment insurance, provincial social assistance, personal income taxes and public spending of different types, and we compare the effects of these policies to the impacts on migration of wages, employment prospects and moving costs. We also conduct a preliminary investigation of the migration consequences of certain extraordinary political events in Quebec and of the closing of the cod fishery in Newfoundland. Unemployment insurance is an especially important and well documented source of income for many people, and regional variation in the generosity of the insurance system over the last three decades has been substantial. The results suggest that while increasing the generosity of the system in high unemployment regions may have induced more migration to the Atlantic region than would otherwise have occurred, the resulting changes in gross flows are probably not large and have had, at most, small effects on average provincial unemployment rates. A variety of other interesting results is also provided.